Enhanching EFL Students’ Reading Comprehension Through KWL (Know,Want And Learned) Strategy - Pratiwi, Melinda Lintang; Fakhruddin, Afief; Nurhidayah, Yayah (Papanda Publisher, 2022)
Students has many problems in reading comprehension are lack of focus on student understanding and making the class passive by teacher, students lack of motivation and students vocabulary difficulties to overcome these problems. Teacher implement know, want and learned (KWL) strategy to enhance students’ reading comprehension. The purpose of research analyze students’ results in reading comprehension towards the use of KWL strategy and to reveal students’ perceptions towards the use of KWL strategy in reading comprehension. In this research conducted at the eveleventh grade of one of senior high schools in academic 2022. The reseacher use qualitative clasroom action research (CAR) as the method of the research in which to identify and to solve the problem on students’ reading comprehension. In this clasroom action research which consided of two cycle and each cycle consisted of four phases, they are planning, acting, observing and reflecting. To collect and analyze the data the reseacher gained the information from observation, questionnaire and based on the result of questionnaire students have a positive perception in reading comprehension using KWL strategy. The students’ result in pre-test and post-test support the data collected, the result the pre – test 1.480 mean was 44.8 in percentages 44,8% and post – test 2.180 mean was 66 in percentages 6,6%. Meanwhile, in this research there is an improvement of students’ reading comprehension by using KWL strategy.